Requirements For Improving The External Audit Quality In Algeria - Ali-abdessamed, Omar (جامعة الوادي - University of Eloued, 2015)
Many questions have been raised about the adequacy of the external audit degree, as well as the factors that are contributing to improve its quality, especially after the institutional collapses which touched the major institutions in the world during the past two decades. Hence, the aim of this study is to raise awareness of the importance of the external audit quality in Algeria through pointing out the reality of its quality after the enactment of law no.10.01, as well as the requirements of its development. The study concluded that the reforms in which the external audit profession witnessed in Algeria have not reached yet the required level, due to the absence of the real activation of the National council of accounting and the other three professional organizations on the ground which affects negatively the external audit quality. Therefore, updating training programs for the Algerian educational systems related to the accounting systems and the audit quality must be pursued, in addition ,activating the accounting organizations and authorities in Algeria and training external auditors while supplying continuous training for them along with providing means to control them, and attempting to develop legislative frameworks and internal laws in the Algerian institutions to ensure the interaction of governance mechanisms in order to improve the external audit quality. أثيرت العديد من التساؤلات حول درجة كفاية التدقيق الخارجي وكذا العوامل التي تعمل على التحسين من جودته وهذا بعد الانهيارات المؤسساتية التي مست كبريات المؤسسات في العالم خلال العقدين الماضيين، إذ تهدف هذه الدراسة إلى محاولة التحسيس بأهمية جودة التدقيق الخارجي في الجزائر من خلال الوقوف على واقع جودته بعد صدور قانون 10/01.وكذا متطلبات تطويره. وخلصت الدراسة إلى أن الإصلاحات التي شهدتها مهنة التدقيق الخارجي في الجزائر لم ترقى بعد للمستوى المطلوب، وهذا نتيجة عدم التفعيل الحقيقي للمجلس الوطني للمحاسبة والمنظمات المهنية الثلاث الأخرى على أرض الواقع بما يخدم جودة التدقيق الخارجي، فلابد من السعي نحو تحديث برامج التكوين للمؤسسات التعليمية الجزائرية وإدخال التطورات المتعلقة بالأنظمة المحاسبية وبجودة التدقيق، بالإضافة إلى تفعيل وتنظيم المنظمات والهيـآت المشرفة على المحاسبة والتدقيق في الجزائر والعمل على تكوين المحترفين والممارسين للمهنة والقيام بالتدريب المستمر لهم مع العمل على توفير وسائل الرقابة عليهم، والعمل على تطوير الأطر التشريعية والقوانين الداخلية في المؤسسات الجزائرية بما يضمن تفاعل آليات الحوكمة من أجل تحسين جودة التدقيق الخارجي
مقال
Keywords: جودة التدقيق الخارجي، قانون 10/01، تفعيل جودة التدقيق الخارجي في الجزائر; auditing quality, Law no.10.1, activating the external audit quality in Algeria